2023
DOI: 10.1186/s12941-023-00564-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of in vitro activities of newer triazoles and classic antifungal agents against dermatophyte species isolated from Iranian University Hospitals: a multi-central study

Abstract: Background Dermatophytes have the ability to invade the keratin layer of humans and cause infections. The aims of this study were the accurate identification of dermatophytes by Polymerase Chain Reaction-Restriction Fragment Length Polymorphism method and sequencing and comparison between the in vitro activities of newer and established antifungal agents against them. Methods Clinical specimens of patients from five Iranian university laboratories … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
0
2
0
2
Order By: Relevance
“…Some other studies [15,18] reported that griseofulvin was the least active antifungal drug against T. mentagrophytes isolates which agrees with the result of the present study. Also, [19] reported in their findings that griseofulvin was the least effective (after fluconazole) against some isolated dermatophytes, including Trichophyton mentagrophytes. As shown in Table 5, even at the highest concentration of 50mg/ml for griseofulvin, the values of the inhibition zone diameters against all the tested dermatophytes were very low for any of them to be considered as susceptible, according to Clinical Laboratory Standard Institute (CLSI) standards.…”
Section: In Vitro Antifungal Susceptibility Testing Using the Antifun...mentioning
confidence: 99%
“…Some other studies [15,18] reported that griseofulvin was the least active antifungal drug against T. mentagrophytes isolates which agrees with the result of the present study. Also, [19] reported in their findings that griseofulvin was the least effective (after fluconazole) against some isolated dermatophytes, including Trichophyton mentagrophytes. As shown in Table 5, even at the highest concentration of 50mg/ml for griseofulvin, the values of the inhibition zone diameters against all the tested dermatophytes were very low for any of them to be considered as susceptible, according to Clinical Laboratory Standard Institute (CLSI) standards.…”
Section: In Vitro Antifungal Susceptibility Testing Using the Antifun...mentioning
confidence: 99%
“…β-Heteroaryl amino alcohols serve as crucial intermediates in the synthesis of various pharmaceuticals and active ingredients, including the antiseizure medication cenobamate, [1] the antifungal agent oteseconazole, [2] itraconazole, [3] fluconazole, [4] miconazole, [5] ketoconazole, [6] the fungicide imazalil, [7] and the transient receptor potential canonical (TRPC) channel antagonist SKF 96365 [8] (Figure 1). In addition, numerous compounds with diverse biological activities, such as antibacterial, [9] anticonvulsant, [10] antitumor, [8] acceleration of hepatocyte proliferation, [11] anti-proliferation [12] (Figure S1), also incorporate βheteroaryl amino alcohols into their structures.…”
Section: Introductionmentioning
confidence: 99%
“…Outro medicamento bastante utilizado contra infecções fúngicas, principalmente contra o gênero Candida é a CASP, pertencente a classe das equinocandinas (Figura 4) (Itoh et al, 2022;Badiee et al, 2023;Thompson et al, 2023). CASP é um dos mais recentes antifúngicos desenvolvidos para a terapia clínica (Sucher et al, 2009).…”
Section: Caspofunginaunclassified
“…Recentemente um trabalho demonstrou que CASP apresentou excelentes resultados contra diversos dermatófitos, especialmente do gênero Trichophyton: T. mentagrophytes, T. rubrum, Trichophyton tonsurans, Trichophyton violaceum, e Trichophyton benhamiae (Badiee et al, 2023). Contra o gênero Microsporum CASP também demonstrou resultados promissores, necessitando baixas concentrações para inibir algumas espécies desse gênero (Katiraee et al, 2021).…”
Section: Caspofunginaunclassified